Explicit exact solutions to some one-dimensional conformable time fractional equations. Issue 1 (2nd January 2019) - Korkmaz, Alper
Abstract: The exact solutions of some conformable time fractional PDEs are presented explicitly. The modified Kudryashov method is applied to construct the solutions to the conformable time fractional Regularized Long Wave-Burgers (RLW-Burgers), potential Korteweg-de Vries (KdV), and clannish random walker's parabolic (CRWP) equations. Initially, the predicted solution in the finite series of a rational form of an exponential function is substituted to the ODE generated from the conformable time fractional PDE using compatible wave transformation. The coefficients used in the finite series are determined by solving the algebraic system derived from the coefficients of the powers of the predicted solution. The solutions for some specific values of the parameters covering derivative order are depicted to explain the wave propagation numerically.